Revisiting the Conditions of Authenticity for Built Heritage in Areas of Conflict - Saifi, Yara; Yüceer, Hülya; Hürol, Yonca (MDPI Multidisciplinary Digital Publishing Institute, 2021)
This article examines the application of conditions of authenticity within the context of built heritage management in areas of political conflict, where heritage management can be seen as a political act rather than a means of protection. It focuses on values attributed to built heritage that can be targeted or reinvented by the dominant power in areas of conflict with minorities being powerless to intervene. The argument is built around the Agios Synesios Church in North Cyprus, which continued to be used by the Greek Cypriot minority following the island division in 1974. Although their way of life has been compromised, they have embraced forced change through using the church to maintain their ritual and religious practices; by doing so, they negotiate their values towards their heritage. In this case, the study shows that the conditions of authenticity are difficult to meet, given the means through which heritage management can be manipulated. Accordingly, the article aims to contribute to general discussions on the vagueness and enigmatic conditions of authenticity in areas of conflict. Different buildings in areas of conflict around the world suffer because of the political nature of heritage management, which makes the criteria of authenticity unviable.
This article exemplifies how heritage management can be manipulated.
Keywords: authenticity; built heritage; heritage management; conflict; Cyprus